INTERNATIONAL TAX PLANNING IN THE CONTEXT OF BEPS IMPLEMENTATION AND DIGITALIZATION OF TAX CONTROL: CHALLENGES FOR SUSTAINABLE DEVELOPMENT OF UKRAINE - Terpytskyi, Eduard (Current Problems of Sustainable Development, 2026)
This article examines current approaches to international tax planning in the context of global changes related to the implementation of the BEPS (Base Erosion and Profit Shifting) Action Plan. Particular attention is paid to the practical aspects of implementing the rules on controlled foreign companies (CFCs) and transfer pricing (TPP) in Ukraine, as well as their impact on taxpayer behavior. Based on data from the OECD, the State Tax Service and the Ministry of Finance of Ukraine, the dynamics of controlled transactions are analyzed, in particular their volume in 2024 (UAH 3.3 trillion), and key industry risks in the field of TPP are identified. The role of digitalization of tax administration, which is gradually changing approaches to control and increasing the transparency of cross-border transactions, is separately considered. The study also draws attention to the use of tax optimization tools — in particular, IP boxes, holding structures and funds — in the context of new requirements for economic presence. Additionally, it is analyzed how the full-scale invasion has affected the international tax strategies of Ukrainian businesses: in particular, through the spread of such approaches as reshoring, friendshoring and decoupling. It is substantiated that the further implementation of BEPS has not only fiscal, but also strategic importance - in particular in the context of currency liberalization, economic recovery and European integration of Ukraine. As a result, key areas of reform are identified, taking into account the requirements of the Global Minimum Tax (Pillar Two), the CRS standard and modern trends in the development of tax and customs control.